Adapting Listening Tactics to Enhance Students’ Performance in Listening Section of National Exam - Alvin Nouval (Jurnal Linguistik Terapan, 2023)
This article focuses on Agustin, an English teacher who is currently teaching listening and speaking skills in Indonesia. Knowing that the new curriculum limits her chance to teach listening, Agustin needs a new idea to prepare her students for the listening section in UN. I believe that adapting listening tactics (Goh, 2002) in the teaching and learning of listening activities is one way to overcome Agustin’s problem. To explain my arguments briefly, I would firstly describe Agustin’s problem. Then, I will address the problem by reviewing some literature related to listening tactics in which I believe could help her. Lastly, I will put the literature into Agustin’s context so that she could determine which tactics are suitable to teach.